(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
The demand for effective, cost-efficient, and environmentally friendly sorbents for dyes and other water contaminants has grown significantly in recent decades. In this study, an underutilised agro waste material Pearl millet straw was used to extract cellulosic fibres. The fibres were modified with monochloroacetic acid (MCA) to impart anionic groups. The effect of carboxymethylation on the physical and chemical properties of PMF was studied using Scanning Electron Microscopy, Fourier Transform Infrared Spectroscopy, and X-ray diffraction (XRD). The adsorption efficiency of native (PMF) and modified PMF (CPMF) in a fixed bed column was studied using breakthrough curves (BTC). Results show that the adsorption efficiency of MB by PMF improves significantly after treatment with MCA. The breakthrough time (tb) increases as the column bed height is increased. However, the adsorption capacity (qₑₓₚ) decreases with increase in bed height. These findings indicate that the carboxymethylation of pearl millet fibres, through physicochemical changes and increased functional group availability, is a simple yet effective approach to substantially enhance their adsorption capacity for MB dye, making CPMF a promising material for cationic dye remediation in water treatment applications. Keywords: Agro waste, Lignocellulosic fibres, Carboxymethylation, Methylene blue, Adsorption, Breakthrough curve.